Impact of tobacco smoking on oral cancer genetics—A next‐generation sequencing perspective. Issue 3 (4th August 2022) - Sharma, Vishwas; Kumar, Dinesh; Kumar, Shravan; Singh, Harpreet; Sharma, Naveen; Gupta, Sanjay
Abstract : This study identified a total of 28 genetic loci (comprising 31 genes), which were found to be altered in oral cancer patients having a habit of tobacco smoking. Three loci, that is, 17p13.1 ( TP53 ), 9p21.3 ( CDKN2A ), and 9q34.3 ( NOTCH1 ) were found to be modified and common in three records whereas one locus, that is, 3q26.32 ( PIK3CA ) was found to be modified and common in two records. This study suggests that oral cancer patients should be categorized into different subgroups based on (i) genetic signatures,  and (ii) smoking status, then the treatment strategies for each group should be precisely defined.